2017
DOI: 10.1093/cercor/bhx188
|View full text |Cite
|
Sign up to set email alerts
|

X-Chromosome Effects on Attention Networks: Insights from Imaging Resting-State Networks in Turner Syndrome

Abstract: Attention deficit hyperactivity disorder (ADHD) is strongly affected by sex, but sex chromosomes' effect on brain attention networks and cognition are difficult to examine in humans. This is due to significant etiologic heterogeneity among diagnosed individuals. In contrast, individuals with Turner syndrome (TS), who have substantially increased risk for ADHD symptoms, share a common genetic risk factor related to the absence of the X-chromosome, thus serving as a more homogeneous genetic model. Resting-state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…For example, there was no significant difference in wFCS between different menstrual phases in healthy females (Syan et al, ). Interestingly, the only two rs‐fMRI studies in TS consistently revealed reduced wFCS in the bilateral intraparietal sulcus and cerebellar regions, relative to healthy controls (Green, Saggar, Ishak, Hong, & Reiss, ; Xie et al, ). Together with our currently observed negative results, the observed wFCS reduction in TS relative to healthy controls is likely associated with the direct genetic effect, rather than the indirect hormonal effect induced by the X chromosome deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there was no significant difference in wFCS between different menstrual phases in healthy females (Syan et al, ). Interestingly, the only two rs‐fMRI studies in TS consistently revealed reduced wFCS in the bilateral intraparietal sulcus and cerebellar regions, relative to healthy controls (Green, Saggar, Ishak, Hong, & Reiss, ; Xie et al, ). Together with our currently observed negative results, the observed wFCS reduction in TS relative to healthy controls is likely associated with the direct genetic effect, rather than the indirect hormonal effect induced by the X chromosome deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, on measures of impulsivity, 39,XO and 40,XX mice did not differ. Thus, the 39,XO genotype appears to have face validity in terms of the attentional deficits observed in TS (Delooz et al, 1993; Green et al, 2018; Mauger et al, 2018; McCauley et al, 1987; Ross et al, 2002; Russell et al, 2006), but not for the impulsivity observed in TS (Romans et al, 1997; Russell et al, 2006; Tamm et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, high levels of BOLD activation in regions associated with emotional empathy are associated with decreased empathic accuracy (Kral et al, 2017). Girls with TS demonstrate functional and structural deficits in regions associated with both cognitive and emotional empathy (Bray et al, 2011;Green et al, 2017;Hong et al, 2014;Marzelli et al, 2011) and, therefore, deficits in empathic accuracy may be related to cortical dysfunction associated with both systems.…”
Section: Discussionmentioning
confidence: 99%
“…Intelligence was measured using the Weschler Abbreviated Scale of Intelligence (WASI; Wechsler, 1999)). Additional recruitment and screening details can be found here (Green et al, 2017). The Stanford University Institutional Review Board (IRB) approved the study and the study was conducted in line with the IRB's standards.…”
Section: Participantsmentioning
confidence: 99%